The Effect of Electronic Mind Mapping Technique on the Enhancement of English Reading Comprehension Among Ninth Grade Students - Al-Awidi, Hamed; Jaradat, Younes (Jordan Journal of Educational Sciences, 2015)
This study aimed to investigate the effect of using the electronic mind-mapping technique (iMindMap) on the enhancement of reading comprehension in English among the ninth grade students in Irbid public schools in Jordan. The sample of the study consisted of two sections of the ninth grade students from two public schools in Irbid first educational directorate during the academic year 2013/2014. Each section consisted of 30 students and the two sections were assigned randomly to an experimental group and a control group. The experimental group was taught English lessons using the electronic mind-mapping technique (IMindMap), while the control group was taught the same lessons by the conventional method. Then a reading comprehension test was applied, and the appropriate statistical techniques were used to analyze data. The results showed a statistical significant difference at the level of (α=0.05) between the means of both groups in favor of the experimental group. Furthermore, the effect size of applying the electronic mind maps in teaching reading texts was medium. Based on the findings, a set of recommendations were given. The main recommendation is to provide teachers in general and English teachers in particular with training workshops to train them in designing electronic mind maps and integrate them in their teaching practices